(untitled) (Educational Knowledge, 2020)
The qualitative study aimed to analyze the factors that lead young adults to consider their lives self-actualized, in order to guide efforts toward promoting holistic development at this stage of life. To this end, resources and obstacles in the development of these factors were described; the phenomenological method was applied, and thematic analysis was used. The research was conducted with twenty-one students from two night schools in Costa Rica, through individual interviews and focus groups.